The Extropy of Concomitants of Generalized Order Statistics from Huang–Kotz–Morgenstern Bivariate Distribution - I. A. Husseiny; A. H. Syam (Journal of Mathematics)
In this paper, we study the extropy for concomitants of m−generalized order statistics (m−GOSs) from Huang–Kotz–Farlie–Gumbel–Morgenstern (HK-FGM) bivariate distribution. Moreover, the cumulative residual extropy (CREX) and negative cumulative extropy (NCEX) are depicted. Furthermore, the empirical technique in conjunction with the concomitant of m−GOS is used to investigate the problem of estimating the CREX and NCEX. The concomitants of order statistics and record values are offered as some applications of these findings.